(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The aging workforce has become a significant concern for modern organizations as the proportion of older workers in the labour force continues to increase. This paper aims to critically examine the evolving concept of Successful Aging at Work (SAW), a crucial framework in the discourse on aging workforces. Understanding and implementing SAW has become increasingly significant for organizations worldwide due to the relatively fast demographic shift towards an increasing share of the older workforce. This literature review synthesizes key research findings, theoretical perspectives, and practical implementations of SAW, drawing on various academic sources. Central to the literature review is exploring the multidimensional nature of SAW, which involves the proactive maintenance and adaptive recovery of older workers’ abilities and motivations. The review also considers various models and classifications of SAW, including the growth/recovery and maintenance framework. Additionally, it examines the intersection of personal development, age-related changes, and organizational strategies within the context of SAW. In conclusion, by integrating insights from diverse academic literature, this review aims to provide a comprehensive understanding of SAW, highlighting its importance in contemporary and future organizational settings. This literature review is a foundational resource for academics, practitioners, and policymakers interested in fostering successful aging at work.